2023
DOI: 10.29105/idcyta.v8i1.29
|View full text |Cite
|
Sign up to set email alerts
|

El fruto de Opuntia oligacantha var. Ulapa, fuente potencial de fitoquímicos

Abstract: Los frutos de Opuntia spp. (xoconostle) son ampliamente consumidos en varias regiones de México, lo que denota su aceptabilidad gastronómica y accesibilidad, por sabor y bajos costos de adquisición. Sin embargo, su calidad nutrimental, y compuestos bioactivos puede cambiar de acuerdo al estado de madurez, condiciones agroclimáticas y variabilidad genética. genética. Es por ello, que el objetivo de esta investigación fué presentar los datos más recientes del xoconostle Ulapa, cultivado en la región de Ulapa de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Regarding the fruit, Gómez-Covarrubias et al [ 36 ] reported lower values for total flavonoids in xoconostle var. joconostle, while López-Palestina et al [ 16 ] reported slightly higher values (4.6 mg QE g −1 DW) in samples of the same variety of xoconostle. This difference may be due to the harvest seasons, which may influence the variability of the results [ 19 ].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Regarding the fruit, Gómez-Covarrubias et al [ 36 ] reported lower values for total flavonoids in xoconostle var. joconostle, while López-Palestina et al [ 16 ] reported slightly higher values (4.6 mg QE g −1 DW) in samples of the same variety of xoconostle. This difference may be due to the harvest seasons, which may influence the variability of the results [ 19 ].…”
Section: Resultsmentioning
confidence: 96%
“…In this sense, the individual component of xoconostle and the mixtures that incorporate this fruit (P-O) displayed better antioxidant activity by DPPH. This is mainly due to the various phenolic compounds with antioxidant capacity ( Table S1 ) with which Opuntia has been related; therefore, although the phenol and flavonoid content did not show the highest values, the fruit may present other compounds with antioxidant activity such as betalains (nitrogenous anthocyanins), which are typical of this fruit [ 16 , 51 ] and may increase antiradical activity when combined with other plants rich in antioxidant compounds, such as Portulaca .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations